E-Commerce Platforms, Social Commerce on Decreasing Visits to the Traditional Market of Cirebon Wholesale Center - Dewi, Atika; Bila, Choerun Nisa Salsa; Maulana, Yono (Green Publisher Indonesia, 2024)
This study uses quantitative research methods to analyze the effect of e-commerce and social commerce platforms on the decline in visits to the Cirebon Wholesale Center Traditional Market, with a focus on the Tiktok Shop case study. The sampling technique used by researchers is non-probability sampling with purposive sampling technique and the data analysis used in this researcher is validity test, reliability test, determination coefficient test, hypothesis testing. Therefore it is important for the government to take more concrete steps to help them deal with this situation, namely by helping to create promotional efforts that can build a positive image for traditional markets, conventional business owners want traditional markets to be known as unique shopping places with quality local products and the friendliness of traders who are the main attraction. with the existence of e-commerce, social commerce and tiktok shop has a significant effect on the decline in interest in visiting the Cirebon Wholesale Center traditional market. As we know in today's modern era, consumer interest in online shopping has a major influence on the marketing management of a company's products and services. Services in e- commerce and social commerce are an alternative for the millennial generation to increase sales turnover compared to offline stores.